Eksplorasi Pengetahuan Matematika Masyarakat dalam Pengolahan Lahan Pertanian - Viviani Patricia J Runtu (Departement of Mathematics Education, 2023)
Exploration of Mathematical Knowledge can be developed as task material in democratic learning. The principle of democratic learning emphasizes the importance of conformity of material and student activities with the experiences and needs of children. This research develops the community's mathematical knowledge to be integrated with materials and activities outside of regular class learning. This study aims to identify mathematical concepts related to agricultural land management and formulate conceptual and procedural application aspects using a context-concept approach. This research quantitatively describes the process indicators and student achievements in learning. The research results include a description of some of the research results showing a significant positive relationship between the mastery of a good relationship between the concept/task material and the concept. The democratic learning concept context approach can increase students' creativity and activeness as well as increase students' understanding of the relationship between mathematical concepts and the context in the surrounding environment.